Proton-induced radiation damage in germanium detectors - Bruckner, J.; Korfer, M.; Wanke, H.; Schroeder, A.N.F.; Filges, D.; Dragovitsch, P.; Englert, P.A.J.; Starr, R.; Trombka, J.I.; Taylor, I.; Drake, D.M.; Shunk, E.R. (IEEE transactions on nuclear science, 1991)
High-purity germanium (HPGe) detectors will be used in future space missions for gamma-ray measurements and will be subject to interactions with energetic particles. To simulate this process, several large-volume n-type HPGe detectors were incrementally exposed to a particle fluence of up to 10/sup 8/ protons cm/sup -2/ (proton energy: 1.5 GeV) at different operating temperatures (90 to 120 K) to induce radiation damage. Basic scientific and engineering data on detector performance were collected. During the incremental irradiation, the peak shape produced by the detectors showed a significant change from a Gaussian shape to a broad complex structure. After the irradiation, all detectors were thoroughly characterized by measuring many parameters. To remove the accumulated radiation damage, the detectors were stepwise-annealed at temperatures of T<or=110 degrees C while kept in their specially designed cryostats. The authors show that n-type HPGe detectors can be used in charged-particle environments as high-energy resolution devices until a certain level of radiation damage is accumulated and that the damage can be removed at moderate annealing temperatures and the detector returned to operating condition.